Effect of manual therapies on cardiac autonomic control: a systematic review - Sousa, Kamila Aparecida de; Cardoso, Leila Batista; Pirola, Flavia Maria; Auad, Luciana Gonzalez; de Oliveira, Adriana Sarmento (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Evidences suggest that manual therapies, a physiotherapy specialty widely used in the treatment of musculoskeletal disorders, would be complementary or alternative for the treatment of cardiac autonomic dysfunction present in the elderly, patients with cardiovascular diseases, some neuromuscular diseases and in some pain processes. Objective: Evaluate the available scientific evidence regarding the effect of manual therapy techniques on cardiac autonomic control. Methods: The selected articles were indexed in the databases PubMed/MEDLINE, SCIELO and LILACS. Results: In the initial search, 233 articles were identified in the electronic databases. After initial analysis of the titles, 210 articles were excluded because they did not address the research topic, performed other types of intervention or evaluation or because they were review articles. A second step of evaluating the 23 previously selected articles was carried out and consisted of reading the abstracts of the articles. After reading the abstracts, 11 were selected. According to the analysis of the selected articles, it was possible to observe that most manual therapy techniques improved the cardiac autonomic control of their samples: Fornari, Carnevali and Sgoifo (2017), Girsberger et al. (2014), Valenzuela et al. (2018), Curi et al. (2017), Akbaş et al. (2019), Buttagat et al. (2009),Kunikata et al. (2012), Mantovani et al. (2005) and Giles et al. (2011). Guilherme et al. (2010) was the only study that found no change. Conclusion: Manual therapies have improved cardiac autonomy acutely in healthy young and middle-aged populations or with discomfort, hypertension and back pain associated with the presence of myofascial trigger points. It is emphasized the importance of conducting new randomized controlled studies, with high methodological quality, that address the effect of other manual therapies on cardiac autonomic control.